Noninactivation of a selectable human X-linked gene that complements a murine temperature-sensitive cell cycle defect. - Brown, C J (1989)
The human gene A1S9T, which complements the temperature-sensitive cell-cycle defect in the murine cell line tsA1S9 and which has previously been assigned to the X-chromosome short arm, is expressed from the inactive X chromosome in human/tsA1S9 somatic cell hybrids grown at the nonpermissive temperature. The Y chromosome cannot complement the defect; thus, unlike at least two other noninactivated X loci, A1S9T has no functional Y-linked homologue. As A1S9T is readily selectable in somatic cell hybrids with the tsA1S9 mouse line, this marker should be useful in isolating somatic cell hybrids containing inactive X chromosomes, or abnormal X's (active or inactive) retaining the short arm.